2008
DOI: 10.1177/0891988707311032
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Correlates of Self-Reported Depression and Self-Reported Cognition Among Patients With Mild Cognitive Impairment

Abstract: Patients with mild cognitive impairment (MCI) frequently experience significant depressive symptomatology and report cognitive disturbances. To date, no studies have examined the relationship between MCI patients' neuropsychologic functioning, self-reported depressive symptoms, and self-reported cognitive difficulties. In this study, 82 MCI patients completed a comprehensive neuropsychological evaluation that included the Beck Depression Inventory (BDI). A subset of 41 patients and informants also completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
3
33
1
1
Order By: Relevance
“…These were assessed using the immediate recall and delayed recall scores from the Hopkins Verbal Learning Test-Revised [27] and the logical memory subtests from the Wechsler Memory Scale -3rd Edition [21] . Consistent with our prior work [28] , we created composite indices for each domain by combining sample-based z-scores that were transformed from the raw test data. For all neuropsychological indices, higher z-scores reflected better performance.…”
Section: Patient Assessmentmentioning
confidence: 99%
“…These were assessed using the immediate recall and delayed recall scores from the Hopkins Verbal Learning Test-Revised [27] and the logical memory subtests from the Wechsler Memory Scale -3rd Edition [21] . Consistent with our prior work [28] , we created composite indices for each domain by combining sample-based z-scores that were transformed from the raw test data. For all neuropsychological indices, higher z-scores reflected better performance.…”
Section: Patient Assessmentmentioning
confidence: 99%
“…For instance, depression, which can be observed in nearly half of individuals with aMCI (Apostolova & Cummings, 2008), has been shown to be associated with the cognitive functioning of these individuals (Dierckx, Engelborghs, De Raedt, De Deyn, & Ponjaert-Kristoffersen, 2007;Bruce et al, 2008;Hudon, Belleville, & Gauthier, 2008). Hudon et al (2008) showed that older adults with aMCI plus depressive symptoms (aMCI-D individuals) were more impaired on tests of executive functions than aMCI individuals with few or no depressive manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on current evidence in the literature (e.g., results from Bruce et al, 2008 revealing that depressive symptoms are associated with better memory performance), our hypotheses are that semantic memory performance will be impaired in both aMCI and aMCI-D participants, but performance will be poorer in the absence of concomitant depressive symptoms. In regards to LLD patients, they will not show a semantic impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Emocije i kognicija nisu odvojeni u kompleksnim mentalnim procesima i ponaĆĄanju, čak imaju i neke zajedničke neuronske krugove 15,16 . Smatra se da smanjenje memorijskih sposobnosti nije sekudarno kao rezultat emocionalnih disfunkcija, zato ĆĄto je memorija oĆĄtećena i kada nema emocionalnih disfunkcija.…”
Section: Uvodunclassified